Effect of Posture in Intraocular Pressure, Comparison between Normal and Glaucomatous Subjects - Shrestha, Ram; Patyal, Sagarika; Bista, Ramesh; Rajkarnikar, Sagar; Gurung, Anu (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Intraocular pressure (IOP) increases when changing from sitting to supine position with an average difference of 0.3 to 6.0mm of Hg. These postural changes of IOP have been found in normal persons, patients with ocular hypertension and normal tension glaucoma. The eye is relatively non-distensible, even small changes in the volume of aqueous humor may significantly change IOP. The increase in resistance in aqueous flow is thought to be the reason for higher IOP in supine compared to sitting position. The aim of this study was to analyze the effects of posture in intraocular pressure in normal and primary open angle glaucoma subjects. Methods: It was a prospective cross sectional study done in Armed Forces Medical College, Pune, between May, 2007 to May, 2009 with sample sized of 60 people (30 controls and 30 Primary open angle glaucoma). Patients underwent complete ocular examination. Two drops of Topical 4% lignocaine were instilled. IOP measurements were taken by Rebound tonometer in sitting and supine positions at 10 min and 30 min interval respectively. Results: Control group (40-76 yrs) and POAG group (40-78 yrs) were found to have a mean rise of IOP of 1.65 and 2 mm of Hg respectively from sitting to lying for 10min, and a mean rise of 2.52 and 5.36 mm of Hg respectively from sitting to lying for 30min. Conclusions: The rise in IOP due to change of posture from sitting to supine positions was significantly higher in glaucomatous patients. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/21-23 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7904